Increase in the incidence of alcoholic pancreatitis and alcoholic liver disease in Iceland: impact of alcohol consumption. - Hauksson, Kristjan; Arnardottir, Margret; Agustsson, Arnar S; Magnusdottir, Berglind A; Baldursdottir, Maria B; Lund, Sigrun H; Kalaitzakis, Evangelos; Björnsson, Einar S (Scandinavian Journal of Gastroenterology, 2020)
To access publisher's full text version of this article click on the hyperlink below Objective: To analyze the incidence of acute alcoholic pancreatitis and of severe alcoholic liver disease (ALD) and its association with per capita alcohol consumption with identification of both alcoholic cirrhosis (AC) and severe alcoholic hepatitis (AH), in a population-based setting.Methods: A search was undertaken in diagnoses database for diagnostic codes in order to find patients hospitalized with incident acute alcoholic pancreatitis (AP) and alcoholic liver disease in Iceland in 2001-2015. Diagnoses were verified in all patients who were retrospectively reviewed. Those with ALD had either AC or AH. Alcohol sales during the study period were obtained from Statistics Iceland.Results: Overall, 273 patients with acute AP, mean age at diagnosis 50 (14) years, 74% males and 159 patients with ALD, mean age 57 (11) years, 73% males, were identified. Mean per capita alcohol consumption was 6.95 (0.4) liters and increased by 21% over the study period. The annual incidence of AP increased from 4.2 per 100.000 to 9.5 and ALD from 1.6 to 6.1 per 100.000. Trend analysis showed a significant annual increase of 7% (RR 1.07, 95%CI 1.04-1.10) for AP and an annual increase of 10.5% (RR 1.10, 95%CI 1.06-1.15) for ALD. The increase was only significant in males.Conclusions: Increase per capita alcohol consumption over a 15 year study period was associated with an increase in the incidence of severe alcoholic liver disease and alcohol-related acute pancreatitis in males but not in females.